(untitled) (Fiep Bulletin - online, 2013)
Worldwide, the demand for blood transfusions has increased as the number of accidents, violence, disease and aging population go up. However, the search for donors has been a constant concern of health authorities. This study aims to draw a profile of blood donors in the nursing graduate students. It is a descriptive study with prospective data and quantitative approach, held at the Department of Nursing at the Federal University of Rio Grande do Norte, at the city of Natal/RN /Brazil, in August 2008. The population was composed by 106 nursing students and data collection took place through a structured instrument. The subject of a study was composed by people at the age group of 18 to 44 years old, with an average of 31 years. As for the sex, consisted of 82.1% female. 82.1% are unmarried, 71.8% of these are donors. There was a predominance of Caucasians (61.1%). About religion, 66.0% say they are Catholics, and 18.5% of these are donors. The largest contingent of family income is between the range of 6 to 10 salaries (43.4%). The frequency at which one donates: 31.8% of the population donates 2 times per year, 27.2% donate when asked, 22.7% donates 3 times last year, 18.1% donates 1 time in year. 54.5% donate for solidarity. We believe that, with this knowledge, we can map out strategies to increase the number of donors in this population. The participation of the population in blood donation becomes essential to the maintenance of stocks, seeking to prevent the demand of applying for blood is greater than its replacement.